FRI0119 TITLE USE OF JAK INHIBITORS IN THE TREATMENT OF RA PATIENTS IN THE ROMANIAN REGISTRY OF RHEUMATIC DISEASES. (2nd June 2020) - Codreanu, C.; Mogosan, C.; Predeteanu, D.; Rednic, S.; Parvu, M.; Rezus, E.; Ionescu, R.
Abstract : Background: JAK inhibitors are the newest therapeutic class available in Romania for the treatment of rheumatoid arthritis (RA). Both available JAK inhibitors (baricitinib and tofacitinib) are fully reimbursed. Objectives: Efficacy and safety data for JAK inhibitors, derived from the Romanian Registry of Rheumatic Diseases (RRBR). Methods: cohort retrospective study, the data being gathered from RRBR, which includes all the patients treated with biologics and targeted synthetic DMARDs in the country. Inclusion criteria: at least one treatment course of JAK inhibitors, until end of 2019. The collected data: demographic and disease characteristics, efficacy parameters (DAS28) and safety data (exposure to JAK inhibitors in person-years (PY) and reported adverse events (AE). Results: the RA cohort treated with JAK inhibitors included 416 patients (7.6% of all RA patients registered in RRBR) exposed to baricitinib (306 pts) or tofacitinib (110 pts) for 66255 PY. The mean age was 57.91 years, 365 (88%) women, 41 (10%) smokers, mean RA duration 11.32 years, 316 (76%) RF positive, 254 (61%) ACPA positive, 356 (85.5%) patients associate a synthetic DMARD, 76 (18%) use steroids (66% <7.5mg prednisone/day); 268 (65%) patients have cardiovascular comorbidities, 84 pts (20%) have modified lipid profile, 89 patients (21.4%) have latent TB, 86 (20.7%) have resolved HBV infection state. JAK inhibitors were the first treatment option for 178 patients (43%), all other patients have been exposed previously to at least one TNF-inhibitor or a biologic with another mode of action, being insufficient responders, as follows: 96 patients – to 1 biologic, 80 patients – to 2 biologics, 30 patients – to 3 biologics, 23 patients – to 4 biologics, 8 patients – to 5 biologics and 1 patient - to 7 molecules before the JAK inhibitors start. Of all patients exposed to JAK inhibitors, 252 (60.5%) patients have continued the therapy since the start summarising 61481PY of exposure. The efficacy parameters reported to this category revealed a mean DAS28 score of 3.08, significantly lower compared to 6 months before (4.77). Regardless the number of biologic agents used before starting a JAK inhibitor, there is no significant difference in DAS28 score when comparing it with DAS28 efficacy of the first treatment option scenario (3.10 vs 2.94, p>0.05). Steroid use, the presence of RF or disease duration have no influence on the efficacy DAS28. On contrary, the ACPA positivity subgroup has a significantly lower DAS28 score, compared to ACPA negativity (3.18 vs 3.82, p<0.05); smoker status has a significantly higher DAS28 compared to non-smokers (3.58 vs 2.94, p<0.05). A total number of 46 AEs were reported for a total exposure of 66255PY. Infections were the most frequently reported AE (0.04/100PY, with 27 events); 6 cases of herpes zoster infection (0.009/100PY, all mild); 3 MACE (0.004/100PY). There were 3 severe adverse events (0.004/100PY) (1 hepatitis non-viral, 2 MACE) with one fatal (acute myocardial infarction). Conclusion: JAK inhibitors represent a safe and efficacious treatment option for patients with active RA. Disclosure of Interests: Catalin Codreanu Consultant of: Speaker and consulting fees from AbbVie, Accord Healthcare, Alfasigma, Egis, Eli Lilly, Ewopharma, Genesis, Mylan, Novartis, Pfizer, Roche, Sandoz, UCB, Speakers bureau: Speaker and consulting fees from AbbVie, Accord Healthcare, Alfasigma, Egis, Eli Lilly, Ewopharma, Genesis, Mylan, Novartis, Pfizer, Roche, Sandoz, UCB, Corina Mogosan Consultant of: Speaker and consulting fees from AbbVie, Novartis, Pfizer, Roche, Sandoz, Speakers bureau: Speaker and consulting fees from AbbVie, Novartis, Pfizer, Roche, Sandoz, Denisa Predeteanu Consultant of: Speaker fee for: Pfizer, Abbvie, Roche, MSD, Speakers bureau: Speaker fee for: Pfizer, Abbvie, Roche, MSD, Simona Rednic: None declared, Magda Parvu Consultant of: Speaker fee and consultant: Pfizer, Novartis, Roche, Abbvie, UCB, Eli-Lilly, Speakers bureau: Speaker fee and consultant: Pfizer, Novartis, Roche, Abbvie, UCB, Eli-Lilly, Elena Rezus: None declared, Ruxandra Ionescu Consultant of: Consulting fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz, Speakers bureau: Consulting and speaker fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz